Synopsis: The changing demographics in Nigeria’s food systems and implications for future youth engagement - Bachewe, Fantu Nisrane; Andam, Kwaw S.; Mawia, Harriet; Popoola, Olufemi (International Food Policy Research Institute, 2025)
Food systems (FS) are critically important in sub-Sahara Africa (SSA), where they account for a significant share of the GDP and employment. FS transformation is both strongly influenced by and strongly influences employment and job creation. This study documents FS employment in the past two decades observed in Nigeria, focusing on changes in demographic structure and inclusiveness. Key findings of the study are: